Similar changes in neuropsychological functioning in english and spanish speaking HIV patients (2018)
Objective: Primary language has been reported to influence the results of neuropsy chological (NP) testing. We sought to determine whether being a primary Spanish versus English speaker affects changes in neuropsychological evaluations in persons living with HIV. Method: Data from 209 (188 English speakers and 21 Spanish speakers) ART-naïve HIV-infected adults were extracted from ACTG A5303, a 48-week randomized clini cal trial of two HIV treatment regimens. Participants’ mean (standard deviation) age and years of education were 35.1 (10.7) and 14.3 (2.7) years respectively. Changes from baseline to week 48 of antiretroviral therapy (ART) in individual, total, and do main z-scores for NP tests and Global Deficit Scores (GDS) were compared between the primary languages using linear regression models, adjusted for baseline scores and years of education. Results: Baseline demographic characteristics were comparable except Spanish speakers had less years of education than the English speakers (p < 0.001). Although differences in some NP measures and domains were detected at baseline, the ad justed changes in individual, total and domain NP z-scores from baseline to 48 weeks of ART were not significantly different between the two primary language groups. The 48-week changes in GDS were also similar. Conclusion: Changes in NP during ART were similar between English and Spanish speaking HIV-infected individuals for all NP measures. This suggests that studies of longitudinal changes in NP can pool participants across these languages